Actinobacteria as Promising Candidate for Polylactic Acid Type Bioplastic Degradation - Butbunchu, Natthicha; Pathom-Aree, Wasu (Frontiers in Microbiology, 2019)
Polylactic acid (PLA) is one of the most commercially available and exploited bioplastics worldwide. It is an important renewable polymer for the replacement of petroleum-based plastic materials. They are both biodegradable and bio-based plastic. Microbial degrading activity is a desirable method for environmental safety and economic value for bioplastic waste managements. Members of the phylum actinobacteria are found to play an important role in PLA degradation. Most of the PLA degrading actinobacteria belong to the family Pseudonocardiaceae. Other taxa include members of the family Micromonosporaceae, Streptomycetaceae, Streptosporangiaceae and Thermomonosporaceae. This mini-review aims to provide an overview on PLA degrading actinobacteria including their diversity and taxonomy, isolation and screening procedures and PLA degrading enzyme production from 1997-2019. Consideration is also given to where to sampling and how we might use these beneficial actinobacteria for PLA waste management.